Capim-pé-de-galinha (Eleusine indica) resistente a herbicidas inibidores da ACCase em áreas algodoeiras de Mato Grosso - Andrade Junior, Edson Ricardo de (2018)
Most of the cotton produced in Mato Grosso comes from large areas of crops, which use herbicides as the main tool in weed management. In recent years there has been an increase in the areas with chemical control failures of Eleusine indica in the cotton plantations, without investigation of the causes. This research aimed to verify the occurrence of Eleusine indica biotypes with resistance to ACCase-inhibiting herbicides in the remaining populations after field applications; to evaluate the degree of resistance and the occurrence of cross-resistance; to identify changes in the ACCase enzyme as a possible mechanism of resistance and to test glyphosate-based herbicide treatments and pre-emergent herbicides for the control of Eleusine indica at field level. The study evaluated 232 samples of Eleusine indica with suspected resistance collected between 2012 and 2016 in all cotton-producing regions of Mato Grosso. Biotypes with resistance to ACCase-inhibiting herbicides were found in all producing regions of the state. Cross resistance and differences in resistance factor (RF), less pronounced among regions and higher among herbicide groups were also found, with RF values being generally higher for haloxyfop than for clethodim and tepraloxydim. The RF was also evaluated in relation to the different development stages of Eleusine indica plants at the time of application, and as for haloxyfop such levels were higher among plants in more advanced stages. At the molecular biology laboratory, genotyping of the biotypes was performed to verify changes in the amino acid sequence of the ACCase enzyme, whereby has been identified, in the resistant biotypes, a mutation that translates into the exchange of an aspartic acid (ASP) by a glycine (Gly) in the position 2078 of the acetyl-CoA carboxylase enzyme, a modification already known as one of the resistance mechanisms to the ACCase-inhibiting herbicides. Several glyphosate-based herbicide treatments, with or without the use of herbicides in preemergence, were efficient for Eleusine indica control, constituting alternatives for the control of biotypes resistant to ACCase-inhibiting herbicides.